2012
DOI: 10.1093/eurpub/cks144
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and sexual health outcomes: a population-based study among 16-44-year-old women in Estonia

Abstract: The exposure of IPV was an important contributor to sexual risk behaviour and adverse sexual health outcomes among women of reproductive age in Estonia. Any strategy to promote sexual health should include prevention of IPV and other forms of violence against women with the strengthening of women's sexual and reproductive rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 22 publications
3
37
2
Order By: Relevance
“…The findings of this study were consistent with results of other studies including systematic reviews of observational studies and clinical trials 7,15,16,18. Various studies based on self-report of STI also reported higher odds of getting STI among women who experienced IPV compared to those not exposed 7,21,22. A randomized controlled trial based on computer-based intervention reported higher incidence of STI (hazard rate ratio 1.68) among women who were exposed to IPV compared to those not exposed 18.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study were consistent with results of other studies including systematic reviews of observational studies and clinical trials 7,15,16,18. Various studies based on self-report of STI also reported higher odds of getting STI among women who experienced IPV compared to those not exposed 7,21,22. A randomized controlled trial based on computer-based intervention reported higher incidence of STI (hazard rate ratio 1.68) among women who were exposed to IPV compared to those not exposed 18.…”
Section: Discussionsupporting
confidence: 91%
“…IPV prevalence varies tremendously from one country to another as shown in the multi-country population-based household surveys carried out by the World Health Organization (WHO), where the prevalence of physical or sexual partner violence or both during past year fl uctuates between as low as 4 % in Japan to 54 % in Ethiopia (Garcia-Moreno et al 2006 ). The rates are also comparable to the ones observed in large population-based studies conducted in primary care settings with a prevalence of past year IPV of 6-21 % (Laanpere et al 2012 ;Xu et al 2005 ).…”
Section: Discussionsupporting
confidence: 81%
“…Violence is known to be associated with poorer psychological adjustment and adverse sexual health outcomes in women. 29 30 In addition, having muscle pain was associated with dyspareunia in the bivariate analysis. This finding is in line with another study showing that musculoskeletal pain often interferes with sex and may be associated with dyspareunia.…”
Section: Discussionmentioning
confidence: 89%